2015
DOI: 10.1177/0363546515577782
|View full text |Cite
|
Sign up to set email alerts
|

Arm Abduction Provides a Better Reduction of the Bankart Lesion During Immobilization in External Rotation After an Initial Shoulder Dislocation

Abstract: Abducting the shoulder during immobilization in external rotation is demonstrated to improve the reduction of the Bankart lesion. Therefore, this position is expected to reduce the recurrence rate after initial dislocation of the shoulder. Future clinical trials are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Moreover, higher compliance rates in the ER group, despite the ER orthosis being less comfortable in some studies, may indicate the presence of bias [ 40 , 44 ]. There was also a substantial difference between the angle of ER, in which coaptation has been proven to be most effective and the greatest angle accepted by patients (45° or 60°, according to different studies versus 10–15°) [ 22 , 37 , 45 47 ]. Several studies confirmed that increasing the degree of external rotation is associated with worse patient discomfort, even when the brace was worn only for periods as short as minutes to hours [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, higher compliance rates in the ER group, despite the ER orthosis being less comfortable in some studies, may indicate the presence of bias [ 40 , 44 ]. There was also a substantial difference between the angle of ER, in which coaptation has been proven to be most effective and the greatest angle accepted by patients (45° or 60°, according to different studies versus 10–15°) [ 22 , 37 , 45 47 ]. Several studies confirmed that increasing the degree of external rotation is associated with worse patient discomfort, even when the brace was worn only for periods as short as minutes to hours [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immobilization in ER and varying degrees of abduction is a new concept that has been studied recently [ 37 , 46 , 47 ]. Here as well, the disproportion between optimal degree of abduction required to achieve coaptation and the degree accepted by patients was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 , 18 The systematic review (which also included these latter two studies) developed by Patrick et al 10 did not show a decrease in recurrence with lateral rotation immobilization. However, in a new study in 2015, Itoi et al 19 show that the best position for injury reduction would be in 30-degree abduction with 60-degree lateral rotation, and that above 30-degree lateral rotation we already find reduction of the anterior lesion, but not of the inferior one. It may be finally argued that the 10–20 degrees of rotation used in the other studies were insufficient for injury reduction.…”
Section: Introductionmentioning
confidence: 91%
“…Another hypothesis is that the joint hematoma would prevent the coaptation of the labrum lesion to its bed, and that the joint drainage could facilitate its coaptation. 10 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%